Designing probiotic-containing fermented food to improve mental disorders derived from childhood emotional neglect - Hevia-Orozco, Jorge; González-González, Cid R. (Frontiers in Sustainable Food Systems, 2023)
Emotional neglect (EN) during childhood is a worldwide problem compromising cognitive functions and mental health. Its scars can be life-lasting and often associated with community violence. Therefore, different approaches are mandatory to reduce its detrimental effects. This review discusses the EN's negative impact on the hypothalamic-pituitary-adrenal axis, its consequences on the immune system, and its subsequent impact on the limbic system. On the other hand, growing evidence shows that gut microbiota affects mental health and vice versa; mental disorders affect microbiota leading to dysbiosis and triggering other metabolic malfunctions. Production of functional fermented foods containing targeted probiotic strains and neuroactive compounds released during fermentation may aid to modulate inflammation via immune processes alleviating anxiety and depressive symptoms and improving cognitive function. Therefore, we propose that tailored probiotic-containing fermented food can improve the mental health of EN victims via immune system modulation.